2022
DOI: 10.1371/journal.pone.0271417
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic and transgenerational effects in spotted-wing Drosophila (Diptera: Drosophilidae) in response to three commonly-used insecticides

Abstract: Although insecticide formulations and spray rates are optimized to achieve lethal exposure, there are many factors in agricultural settings that can reduce the effective exposure of insect pests. These include weather patterns, timing of application, chemical degradation/volatilization, plant structural complexity, and resistant populations. While sub-lethal exposure to insecticides can still have negative impacts on pest populations, they can also lead to stimulatory, or hormetic, responses that can increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…For instance, Krüger et al [49] conducted a study on D. suzukii, disclosing that a neurotoxic insecticide with action on insect coordination was, however, able to positively affect mating when applied at sublethal doses. Similarly, a study developed by Deans and Hutchison [50] on SWD revealed evidence of the hormesis response to sublethal doses of the insecticides zeta-cypermethrin, spinetoram, and pyrethrin. This study also described survival as being sex-dependent, as males were more susceptible to insecticides than females.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, Krüger et al [49] conducted a study on D. suzukii, disclosing that a neurotoxic insecticide with action on insect coordination was, however, able to positively affect mating when applied at sublethal doses. Similarly, a study developed by Deans and Hutchison [50] on SWD revealed evidence of the hormesis response to sublethal doses of the insecticides zeta-cypermethrin, spinetoram, and pyrethrin. This study also described survival as being sex-dependent, as males were more susceptible to insecticides than females.…”
Section: Discussionmentioning
confidence: 85%
“…More research will be needed to determine if additional impacts on adult nutrition exist. In addition, understanding the interplay between nutrition and insecticide resistance will be important, as D. suzukii has demonstrated a propensity to develop resistance to spinosad and zeta‐cypermethrin (Deans & Hutchison, 2022a, 2022b; Ganjisaffar et al, 2022; Gress & Zalom, 2019). Elucidating how nutritional plasticity can affect the evolution of resistance but also whether resistant population have different intake targets will be necessary for better understanding mechanisms of resistance and for making sure relevant diets are used in resistance monitoring bioassays (Deans et al, 2017; Shikano & Cory, 2014a, 2014b).…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of Mustang Maxx® for D. suzukii control is quite high, as it maintains reasonably high residual contact against adults under field conditions. However, issues with ensuring effective contact with adult D. suzukii have been observed in field‐applications, particularly structurally‐complex cultivars such as caneberries 23–25 . Spinetoram (Delegate® WG), produced by Corteva Agriscience (Indianapolis, IN, USA), is a fermentation product of the soil bacterium Saccharopolyspora spinosa and an analog to spinosad (IRAC Group 5) insecticides 26 .…”
Section: Methodsmentioning
confidence: 99%
“…However, issues with ensuring effective contact with adult D. suzukii have been observed in field‐applications, particularly structurally‐complex cultivars such as caneberries. 23 , 24 , 25 Spinetoram (Delegate® WG), produced by Corteva Agriscience (Indianapolis, IN, USA), is a fermentation product of the soil bacterium Saccharopolyspora spinosa and an analog to spinosad (IRAC Group 5) insecticides. 26 It causes morbidity by disrupting nicotinic/gamma amino butyric acid (GABA)‐gated chloride channels.…”
Section: Methodsmentioning
confidence: 99%